Governansi Kolaboratif Dalam Praktik Keimigrasian Di Indonesia: Tantangan Dan Peluang Di Tingkat Regional Indonesia - Bahrul Ulum; Seno Setyo Pujonggo; Agung Sulistyo Purnomo (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to analyze the practice of collaborative governance in immigration management in the border region of North Kalimantan, Indonesia, using the Collaborative Governance framework proposed by Ansell and Gash (2008). Employing a descriptive qualitative approach based on literature review, the findings reveal that current collaborative practices remain partial and are predominantly characterized by administrative cooperation rather than substantive, iterative collaboration. Key barriers include unequal institutional capacities, non-inclusive institutional design, lack of facilitative leadership, and limited trust and open communication among stakeholders. Although formal forums such as TIMPORA have been established, collaboration still relies heavily on personal relations and lacks an integrated information system. The study recommends strengthening institutional design, enhancing resource capacities, and fostering collaborative leadership that emphasizes sustainability and transparency.